EMERGING THERAPEUTIC AND DIGITAL INNOVATIONS IN CYSTIC FIBROSIS: A COMPREHENSIVE REVIEW - Gabriela Mroczka; Paulina Łobaza; Idalia Myszor; Michał Madej; Maria Kubacka; Lucjan Kocemba; Sylwia Nycz-Jucha; Brygida Pinkowicz; Piotr Rachwał; Barbara Nowak-Misiąg (International Journal of Innovative Technologies in Social Science, 2026)
Cystic fibrosis (CF) is an autosomal recessive, multisystem genetic disorder caused by mutations in the CFTR gene, leading to defective chloride transport across epithelial surfaces. Historically associated with early mortality, CF care has transformed over the last decade due to CFTR modulator therapies that target the underlying protein defect, significantly improving pulmonary function, reducing exacerbations, and enhancing quality of life. Concurrently, digital health technologies such as telemedicine, remote monitoring, artificial intelligence (AI) facilitated predictive tools, and wearable sensors are reshaping care delivery. Additionally, advances in gene therapy and personalized medicine hold potential for future curative approaches. This review synthesizes current evidence on CFTR modulators, emerging therapeutic strategies, the integration of digital health in CF care, and the psychosocial and economic challenges that persist. We provide a holistic perspective on how these developments collectively advance CF management, and we highlight ongoing research directions to further improve outcomes.